Direct solar steam generation inside evacuated tube absorber - Khaled M. Bataineh (AIMS Energy, 2016)
Direct steam generation by solar radiation falling on absorber tube is studied in this paper. A system of single pipe covered by glass material in which the subcooled undergoes heating and evaporation process is analyzed. Mathematical equations are derived based on energy, momentum and mass balances for system components. A Matlab code is built to simulate the flow of water inside the absorber tube and determine properties of water along the pipe. Widely accepted empirical correlations and mathematical models of turbulent flow, pressure drop for single and multiphase flow, and heat transfer are used in the simulation. The influences of major parameters on the system performance are investigated. The pressure profiles obtained by present numerical solution for each operation condition (3 and 10 MPa) matches very well experimental data from the DISS system of Plataforma Solar de Almería. Furthermore, results obtained by simulation model for pressure profiles are closer to the experimental data than those predicted by already existed other numerical model.